Enhancement of the electrochemical capacitors of porous carbon from cross-linked polymers through heteroatoms and cobalt incorporation - Manyala, Ncholu I. (University of Pretoria, 2023)
Thesis (PhD (Physics))--University of Pretoria, 2023.